Spontaneous calcific coronary embolisation: necropsy x-ray study. Issue 10 (October 1980) - Steiner, I; Hlava, A
Abstract : Thirty-one hearts with advanced calcification of one or both left heart valves were investigated for the presence of spontaneous calcific emboli. X-ray (Mammograf) showed coronary emboli in 14 cases, that is, in 45% of the whole series. In seven cases (23%) calcific particles were also present in the left ventricular cavity. A total of 265 calcific emboli (205 intracoronary plus 60 intravenous) was demonstrated. The embolisation occurred most frequently and most extensively in association with postrheumatic mitral valve disease. Coronary calcific embolisation must be considered in the differential diagnosis of symptoms of ischaemic heart disease in patients suffering from valvular heart lesions.